Complete Genome Sequence and Genome Analysis of Eggplant mottled dwarf virus‐Iranian Isolate. Issue 5 (2nd May 2014) - Babaie, Ghobad; Kouhi Habibi, Mina; Massah, Amir; Dizadji, Akbar; Izadinejad, Laleh; Simon, Anne
Abstract The full‐length nucleotide sequence of the Iranian isolate of Eggplant mottled dwarf virus (EMDV), a phytorhabdovirus, was determined using the random polymerase chain reaction method (rPCR) followed by PCR with specific primers to fill in the gaps. The negative‐sense RNA genome of the Iranian isolate of EMDV contains 13154 nucleotides and seven open‐reading frames (ORFs) in the order 3′‐leader‐N‐X‐P‐Y‐M‐G‐L‐trailer‐5′. These ORFs encode the nucleocapsid, X protein (of unknown function), phosphoprotein, Y protein (putative movement protein), matrix protein, glycoprotein and RNA‐dependent RNA polymerase, respectively. EMDV has a 199 nt 3′ leader RNA and a 151 nt 5′ trailer, and the ORFs are separated by conserved intergenic sequences. Phylogenetic analyses indicate that EMDV is most closely related to Potato yellow dwarf virus, which has a distinctly different geographical distribution.